2021
DOI: 10.1016/j.amsu.2021.103130
|View full text |Cite
|
Sign up to set email alerts
|

The mystery of COVID-19 reinfections: A global systematic review and meta-analysis

Abstract: Background As the COVID-19 pandemic rages on, reports on disparities in vaccine roll out alongside COVID-19 reinfection have been emerging. We conducted a systematic review to assess the determinants and disease spectrum of COVID-19 reinfection. Materials and methods A comprehensive search covering relevant databases was conducted for observational studies reporting Polymerase Chain Reaction (PCR) confirmed infection and reinfection cases. A quality assessment tool deve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
30
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 105 publications
(118 reference statements)
8
30
2
Order By: Relevance
“…It is interesting to note that this cohort of cases had mild symptoms or were asymptomatic (93.5%). This is comparable to results from a systemic review of reinfection cases, stating that 75% of cases were categorized as "mildly symptomatic" 11 . However, asymptomatic infection was 42.1% among fully vaccinated vs. 32.8% among those who were not vaccinated.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is interesting to note that this cohort of cases had mild symptoms or were asymptomatic (93.5%). This is comparable to results from a systemic review of reinfection cases, stating that 75% of cases were categorized as "mildly symptomatic" 11 . However, asymptomatic infection was 42.1% among fully vaccinated vs. 32.8% among those who were not vaccinated.…”
Section: Discussionsupporting
confidence: 80%
“…After genetic analysis, the authors concluded that the genetic variation between the two SARS-CoV-2 specimens was too signi cant to be explained by short-term in vivo evolution. Currently, there are over 900 studies published regarding reinfection in COVID-19 11 , highlighting the genuine possibility of reinfection that needs to be taken into account by researchers and policymakers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ]. Furthermore, there is an increasing number of reports concerning the reinfection of people previously infected with SARS-CoV-2 [ 14 , 15 , 16 ]. The actual numbers of SARS-CoV-2 infections are difficult to estimate due to asymptomatic or mild disease courses.…”
Section: Introductionmentioning
confidence: 99%
“…In those cases, there was a higher reinfection rate in older adults, which was also associated with an increase in pulmonary complications and hospital stays. 5 - 7 …”
Section: Discussionmentioning
confidence: 99%
“…Worldwide studies, carried out in more than 22 countries, have observed that there are significant differences in reinfection cases with respect to the initial infection, finding that 75% had mild symptoms and showing an increase in asymptomatic cases for second episode when compared to the first (9.2% vs 31.9%). 7 …”
Section: Introductionmentioning
confidence: 99%